Circulating CD200 is increased in the secretory phase of women with endometriosis as is endometrial mRNA, and endometrial stromal cell CD200R1 is increased in spite of reduced mRNA. (23rd November 2022) - Hamilton, Matthew; Turpin, Victoria; Ayoub, Anmar; Reihani, Amir; Arredondo, Jorge; Ask, Kjetil; Clark, David A.; Foster, Warren G.
Abstract: Problem: Estrogen‐dependent extrauterine implantation and growth of menstrual endometrial tissue affects roughly 10% of reproductive age women and depends on suppression of local innate immune defenses to prevent ectopic tissue rejection. Immunohistochemistry has shown the immune check‐point inhibitor CD200 which can suppress rejection is expressed in eutopic endometrium and in ectopic deposits. Soluble CD200 accumulated in venules draining eutopic and ectopic endometrium of endometriosis cases in the secretory phase but not proliferative phase of the menstrual cycle, and should be increased in the circulation. Method of Study: Sera from endometriosis and non‐endometriosis controls were tested by ELISA for CD200. Endometrial CD200, CD200R1 and CD200R2 mRNA in eutopic was quantified by RT‐PCR and localized by in situ hybridization. CD200R1 protein was quantified by immunohistochemistry. Results: Secretory phase serum CD200 was elevated in women with endometriosis compared to controls. Serum CD200 correlated with matched endometrial CD200 mRNA levels. Expression of mRNA for CD200R1 which signals immune suppression was decreased whereas mRNA for the CD200R2 activating receptor was increased. In situ staining of CD200R1 and CD200R2 mRNA showed both receptors were expressed and the fraction of CD200R that is CD200R1 was reduced in secretory and menstrual phase endometriosis endometrium consistent with the RT‐PCR result. By contrast, CD200R1 protein and CD200R1 fraction of total CD200R protein were increased in endometriosis. Conclusions: Failure to suppress circulating CD200 levels in the secretory phase had an 87% specificity and 90% sensitivity for endometriosis. CD200 and increased CD200R1 expression may facilitate development of ectopic deposits by suppressing rejection mechanisms.